1980
DOI: 10.1007/bf00117220
|View full text |Cite
|
Sign up to set email alerts
|

Structure of mean winds and turbulence in the planetary boundary layer over rural terrain

Abstract: A detailed analysis has been carried out of the temporal and spatial structure of mean winds and turbulence in the neutrally-stable planetary boundary layer over typically rural terrain. The data were obtained from a horizontal array of tower-mounted propeller anemometers (z = 11 m) during a five-hour period for which the mean wind direction was virtually perpendicular to the main span of the array. Various turbulence characteristics have been obtained for all three components of velocity and have been compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
42
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(46 citation statements)
references
References 22 publications
4
42
0
Order By: Relevance
“…The average separation of the anemometers on this grid was about 20 m. Assuming an exponential shape for the spatial correlation coefficient between wind speeds, Hayashi (1991) derived integral distance scales of 75 m and 25 m for along-wind and cross-wind directions, respectively. Teunissen (1980) derived similar values of the integral scales in an independent experiment. In general, the correlation coefficients between the winds at a given location and the winds at the center of Hayashi's network had dropped to about 0.3 to 0.5 at the edge of the network.…”
Section: Previous Studies Of Mesoscale Wind Variabilitysupporting
confidence: 49%
“…The average separation of the anemometers on this grid was about 20 m. Assuming an exponential shape for the spatial correlation coefficient between wind speeds, Hayashi (1991) derived integral distance scales of 75 m and 25 m for along-wind and cross-wind directions, respectively. Teunissen (1980) derived similar values of the integral scales in an independent experiment. In general, the correlation coefficients between the winds at a given location and the winds at the center of Hayashi's network had dropped to about 0.3 to 0.5 at the edge of the network.…”
Section: Previous Studies Of Mesoscale Wind Variabilitysupporting
confidence: 49%
“…where v = w = 0 m·s −1 [19]. Unless the scanning beam is perpendicular to the flow, the mean velocity of the along-beam component verifies v r = 0 m·s −1 .…”
Section: Data Processingmentioning
confidence: 87%
“…The integral scale can be defined in several ways: the larger scale of the flow, or the scale above which the Fourier transform has a slope inferior to a −5/3 slope, such as where the turbulent kinetic energy (TKE) is maximum. Micrometeorological studies have found integral scales varying in a huge range, from around 100 to 1000 m (Teunissen, 1980;Kaimal and Finnigan, 1994).…”
Section: Introductionmentioning
confidence: 99%